The Impact of Preceptorship Program on Turnover Intention of Fresh Graduate Nurses in Hospital - Vera Rodessa; Anwar Kurniadi; Agustinus Bandur (Babali Health, 2020)
Introduction: The transition period in the first year of nursing career is a difficult time for new nurses to adapt. The transition process for a new nurse is known as the Duchscher's transition shock model. Almost all hospitals worldwide have experienced difficulties with regards to the ability of new nurses to adapt to profession. The Preceptorship is a program designed to help new nurses adapt during the transition. This study aims primarily at exploring the impacts of the program to the turnover intention of fresh graduate nurses working in hospital. Methods: For this major purpose, a qualitative research with particular reference to phenomenology design was applied. Accordingly, this research applied in-depth interviews with active participation of 13 key informants. The informants are fresh graduate nurses employed in two private hospitals in Jakarta. Results: The results of thematic and cross-case analysis with N Vivo v.12 indicate four themes: preceptorship process, experiences in transition, problem arising during transition period and preceptorship program in helping nurse. Conclusion: It is found that nurses aged 22 years old and 7 months of working experience are the most likely to resign. The experience of new nurses undergoing to transition period affects 48% of their desire to leave work. This study recommends conducting further research on what kind of work environment is ideal for facilitating adaptation for new nurses.